TAKRADHARA THE DIVINE PROCEDURE FOR IMPROVING QUALITY OF THE SLEEP - Poonam, *Mohod; Sharad, Mohod; S, Shivani; Kirandeep, Kour (International Journal of Ayurveda and Pharma Research, 2015)
Nidra (sleep) in Ayurveda plays very important role in health point of view hence it is necessary to have a sound sleep. Current study determines the efficacy of Takradhara and indigenous drugs in administration of Anidra (insomnia). It was a simple, random, systematic, and focused group study with sample size 30.It was observed that the common causes of Anidra are mental stress; Chinta, Bhaya, Krodha, and improper sleep timings with having common symptoms like Yawning, Drowsiness, Fatigue, Malaise and Headache.It was seen that after completion of the course 73% of the patients got relieved from drowsiness, 72% relieved from headache, 67% relieved from malaise, 60% relieved from yawning and 58% of the patients got relieved from fatigue. Apart from that, 43% of the patients show improvement in the luster, 42% got relieved from constipation and 41% relieved from indigestion. However, 39% improved their concentration, 37% improved their level of perception and 27% improved their memory, while 23% of the patients show improvement in their weight.Therefore it can be concluded that the procedure of Takradhara was very safe and efficacious to treat the modalities and can be used effectively on the management of Anidra. Mixture prepared for Takradhara was found very effective in the management of Anidra. It only reduces stress and tension but also enhances the circulation of brain, improves memory, nourishes the hair on scalp, calms the mind and body and helps to beat insomnia.